2013
DOI: 10.1096/fj.13-229054
|View full text |Cite
|
Sign up to set email alerts
|

A novel effector secretion mechanism based on proton‐motive force‐dependent type III secretion apparatus rotation

Abstract: The type III secretion apparatus (T3SA) participates in the secretion of bacterial proteins called effectors, although the detailed mechanism of effector secretion remains unclear. T3SA and flagellum were shown to branch from a common ancestor and also show structural similarity. In addition, both T3SA-dependent effector secretion and flagellar rotation were reported to require proton-motive force (PMF) for activity. From these reports, we hypothesized that T3SA, like the flagellum, would rotate via PMF and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…However, they are visible in spirochaetes with periplasmic filaments [48], which rotate at high load. No equivalent proteins have been detected in injectisomes, and although there is a report of rotation of the injectisome needle tip [49], this observation has so far not been repeated or functionally linked to any T3SS component.…”
Section: Structural and Functional Homologies Among The T3ss And Othementioning
confidence: 93%
“…However, they are visible in spirochaetes with periplasmic filaments [48], which rotate at high load. No equivalent proteins have been detected in injectisomes, and although there is a report of rotation of the injectisome needle tip [49], this observation has so far not been repeated or functionally linked to any T3SS component.…”
Section: Structural and Functional Homologies Among The T3ss And Othementioning
confidence: 93%
“…These include polymers, proteins and polypeptide mimics. Ohgita et al (89) reported that the proton-motive force dependent rotation of the Pseudomonas T3SS was inhibited by the addition of the viscous polymer polyethylene glycol (PEG) 8000 and this was hypothesized to occur by the resistance of physical rotation due to solution viscosity. This hypothesis was further supported by a follow up study showing that other viscous polymers, such as alginate and mucin, inhibited T3SS rotation while low viscosity polymers such as PEG200 do not (90).…”
Section: Non-small Molecule Inhibitors Of T3ssmentioning
confidence: 99%
“…Intriguingly, especially in light of the ATPase complex structures, a recent study has suggested a proton-motive force dependent rotation of the NF-T3SS needle filament, thereby drawing further parallels to the flagellum [61 •• ] and the latest work proposing a general mechanism for flagellar export [62 •• ] may therefore also provide insight into the NF-T3SS. Future research concerning the molecular mechanisms of assembly and secretion by these nanomachines will undoubtedly provide further insight into the extent of the diversification of T3SSs.…”
mentioning
confidence: 99%